(untitled) (International Journal of Current Engineering and Technology, 2014)
With the exponential growth in web users, search history is also growing exponentially. To manage the web search , search engine uses different techniques. It gives users an easy feel to search their interest by providing page ranking, web personalization and other tools. Most of the search engines store search history in search query and respective click format. We are using query grouping mechanism to store user’s history so that she will get her previous related searched data easily.